Educational significance of Amir Temur’s teachings - Charos Avazova (Zien Journals, 2022)
For centuries, there have been great beings who have come into the world, whose universal activity affects not only the fate of one nation, but the fate of all mankind and world civilization. Among many historical figures, the name of the great commander Amir Temur deserves special mention. His teachings serve as important guidelines for government politicians, for every rising generation, and for humanity as a whole.
Keywords: Harmoniously developed generation; upbringing; kingdom; event